Penguatan Kapasitas Perpustakaan Daerah Provinsi Kepulauan Riau Dengan Pendekatan Systemic Capacity Building - Firman, Firman; Agus Hendrayady; Wayu Eko Yudiatmaja; Wahjoe Pangestoeti; Okky Rizki Azizi (Politeknik Negeri Jember, 2024)
Local libraries are educational, research and public service institutions that function as information and knowledge centers at the local level. By providing access to various types of information and knowledge, these libraries play an important role in supporting the progress of local communities and government. Regional libraries in Riau Islands Province can face a variety of significant problems when increasing their capacity, including; Lack of resources, both in terms of budget, labor, and book collections, is a major problem (Scupola & Zanfei, 2016). The implementation method in activities by conducting observations and data searches to agencies or stakeholders in the form of scientific education or FGDs to ensure the objectives of this activity are successful. In an effort to strengthen the capacity of the regional library of the Riau Islands province carried out in the time span from April to November 2024. The results of activities are expected that the Riau Islands provincial library is now better prepared to face challenges in the digitalization era and meet the growing information needs of the community.